ANALYSIS OF FACTORS AFFECTING PRODUCTION RICE IN LANGKAT REGENCY WITH METHODS BACKWARD IN MULTIPLE LINEAR REGRESSION YEAR 2018 - Diah Reka Putri; Rima Aprilia; Riri Syahfitri Lubis (Journal of Mathematics and Scientific Computing With Applications, 2021)
Rice is a food crop that is needed by the people of Indonesia, because the riceplant as a producer of rice that can be processed as a staple food for thepopulation in Indonesia. Factors considered to have an effect on lowland riceproduction in Langkat Regency are: yearend crop residues, land area, rainyday rainfall, seeds, and fertilizers. In determining the factors that greatlyinfluence the production of lowland rice, it is necessary to use multiple linearregression equations such as using the method backwards. That is, where all Xvariables are regressed with Y variables.